2021
DOI: 10.1016/j.paid.2021.111110
|View full text |Cite
|
Sign up to set email alerts
|

The relationship of perceived social support to feelings of hopelessness under COVID-19 pandemic: The effects of epidemic risk and meaning in life

Abstract: Lockdown orders were issued on January 23, 2020 in Wuhan, China, for the purpose of preventing and controlling COVID-19, which led to severe psychological problems for residents. The present study aimed to investigate the recovery model of hopelessness through interpersonal pathways during the COVID-19 epidemic. An online survey was conducted in 34 provinces (those in autonomous regions and municipalities) of China. This survey investigated residents' hopelessness and the impact of three factors on it, includi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(37 citation statements)
references
References 49 publications
2
21
0
3
Order By: Relevance
“…Third, social support has a significant moderating effect on the relationship between risk expectation and farmers' confidence in agricultural production recovery. Government support, support from relatives and friends, and financial support all play a moderating role in the relationship between risk expectation and confidence in recovery; this is similar to the findings of previous studies; for example, Zuo et al [101] showed that social support could work as a protective factor in alleviating homelessness. Kaniasty et al [31] stressed that salutary direct effects of supportive behaviors on post-disaster psychological distress were also highly evident.…”
Section: Discussionsupporting
confidence: 87%
“…Third, social support has a significant moderating effect on the relationship between risk expectation and farmers' confidence in agricultural production recovery. Government support, support from relatives and friends, and financial support all play a moderating role in the relationship between risk expectation and confidence in recovery; this is similar to the findings of previous studies; for example, Zuo et al [101] showed that social support could work as a protective factor in alleviating homelessness. Kaniasty et al [31] stressed that salutary direct effects of supportive behaviors on post-disaster psychological distress were also highly evident.…”
Section: Discussionsupporting
confidence: 87%
“…Zuo et al ( 2021 ) investigated the impact of perceived social support, meaning in life, and epidemic risk levels on hopelessness. The results showed perceived social support and meaning in life to negatively predict hopelessness.…”
Section: Hopelessnessmentioning
confidence: 99%
“…Moreover, lockdowns imposed during the COVID-19 pandemic have resulted in the sudden interruption of routine educational and leisure activities, which are indispensable for the youths’ development ( de Abreu et al., 2021 ; Cattelino et al., 2021 ). These radical and unpredictable changes have contributed to a significant rise in perceived insecurity ( Zuo et al., 2021 ; Wen et al., 2021 ), which in turn induce long-term negative consequences on the well-being of adolescents and young adults ( Morelli et al., 2020 ; Inanc, 2018 ; Nica et al., 2016 ).…”
Section: Introductionmentioning
confidence: 99%
“…As the pandemic progresses, the youth's subjective well-being is highly likely to be impaired due to the insecurity developed from the sudden changes in their daily lives ( Zuo et al., 2021 ; Wen et al., 2021 ). Insecurity is broadly defined as the premonition of possible psychological or physical risks ( Greenhalgh and Rosenblatt, 1984 ), including the dimensions of interpersonal security and sense of control ( An et al., 2004 ; Zhou et al., 2018 ; Wen et al., 2021 ).…”
Section: Introductionmentioning
confidence: 99%